2012
DOI: 10.1109/tnsre.2012.2190942
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Loop for Memory Prosthesis: Detecting the Role of Hippocampal Neural Ensembles Using Nonlinear Models

Abstract: A major factor involved in providing closed loop feedback for control of neural function is to understand how neural ensembles encode online information critical to the final behavioral endpoint. This issue was directly assessed in rats performing a short-term delay memory task in which successful encoding of task information is dependent upon specific spatiotemporal firing patterns recorded from ensembles of CA3 and CA1 hippocampal neurons. Such patterns, extracted by a specially designed nonlinear multi-inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 74 publications
(124 reference statements)
2
54
1
Order By: Relevance
“…This is not surprising given that the primary output of both regions is provided by principal cells. In fact, the set of highly predictive principal cells may correspond to the so-called functional cell types which selectively fire in response to a specific type of stimulus in the DNMS task (ie left-nonmatch) (Hampson et al, 1999, 2012a,b; Goonawardena et al, 2010). Given that these cells are found both in CA3 and CA1 it is clear that these cells would have predictive power over each other.…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising given that the primary output of both regions is provided by principal cells. In fact, the set of highly predictive principal cells may correspond to the so-called functional cell types which selectively fire in response to a specific type of stimulus in the DNMS task (ie left-nonmatch) (Hampson et al, 1999, 2012a,b; Goonawardena et al, 2010). Given that these cells are found both in CA3 and CA1 it is clear that these cells would have predictive power over each other.…”
Section: Resultsmentioning
confidence: 99%
“…19.4d) as a function of trial difficulty (number of images) on MIMO stimulation versus nonstimulation trials. The controls associated with these results are found in Hampson et al (2012b).…”
Section: Facilitation Of Pfc Columnar Processing By Mimo Microstimulamentioning
confidence: 78%
“…In prior studies (Berger et al 2011;Hampson et al 2012bOpris et al 2013), it has been shown that a multi-input multi-output model (MIMO) nonlinear dynamic model applied to spatiotemporal patterns of multiple recordings from synaptically connected neurons is capable of extracting patterns of firing related to successful task performance of this same task shown in Fig. 19.1a.…”
Section: Application Of the Mimo Model To Pfc Columnar Processingmentioning
confidence: 99%
“…The nonlinear multi-input, multi-output model (MIMO) is an effective predictor of hippocampal memory encoding (Hampson et al, 2012), and it has been successfully used as a neuroprosthetic to improve memory performance in both rats (Hampson et al, 2012) and nonhuman primates (Hampson et al, 2013). FCTs have been shown to significantly contribute to the MIMO hippocampal model (Hampson et al, 2012) suggesting that behavioral correlates of individual hippocampal neurons exhibit nonlinear and possibly fractal features in their spike trains.…”
Section: Introductionmentioning
confidence: 99%
“…FCTs have been shown to significantly contribute to the MIMO hippocampal model (Hampson et al, 2012) suggesting that behavioral correlates of individual hippocampal neurons exhibit nonlinear and possibly fractal features in their spike trains. Hippocampal neuronal ensembles have previously been pre-screened using z -score based FCT identification, but since this method employs subjective decisions during computation, it is hypothesized that multifractal analysis could provide an objective measure of the information processing capacity of hippocampal neurons.…”
Section: Introductionmentioning
confidence: 99%